2009
DOI: 10.1111/j.1365-2605.2008.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Semen characteristics and inflammatory mediators in infertile men with different clinical diagnoses

Abstract: This study was aimed at investigating whether semen characteristics in different clinical diagnoses of infertility are associated with PMN elastase, IL-6, IL-8, IL-1beta and TNFalpha levels detected in seminal plasma. Sixty-eight patients were divided into groups according to their clinical diagnosis: idiopathic infertility (group I), varicocele with infections (group II), varicocele (group III), infections (group IV), controls (group V). Physical examination and scrotal Eco-color Doppler was used to detect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
67
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 30 publications
(72 reference statements)
3
67
1
Order By: Relevance
“…Heat stress leads to ROS production, which is suggested to act as a cytotoxic agent to germ cells and sperm (47). Additionally, a growing body of evidence has suggested that male reproductive tract infections and inflammation are directly associated with semen oxidative stress (9,(40)(41)(42)(43)(44). More than 15% of infertile men have genitourinary infections or inflammation (48).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Heat stress leads to ROS production, which is suggested to act as a cytotoxic agent to germ cells and sperm (47). Additionally, a growing body of evidence has suggested that male reproductive tract infections and inflammation are directly associated with semen oxidative stress (9,(40)(41)(42)(43)(44). More than 15% of infertile men have genitourinary infections or inflammation (48).…”
Section: Discussionmentioning
confidence: 98%
“…Studies have demonstrated that the main causes of semen oxidative stress are heat stress and immune response (9,(38)(39)(40)(41)(42)(43)(44). Heat stress is caused by an increase in scrotal temperature, which may be due to varicocele (38), obesity (45), or lifestyle factors, such as work seated for long periods (46).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…13 It has been proved that AAT-D could favor the deterioration of spermatozoids. 14 The mechanisms involved could be associated with an increase in inflammatory activity, because it is known that there is a decrease in fertility in men with inflammatory diseases. 15 In our patient, probably the epididymal cysts observed in both caputs may be related to the AAT-D.…”
Section: Discussionmentioning
confidence: 99%
“…14 The mechanisms involved could be associated with an increase in inflammatory activity, because it is known that there is a decrease in fertility in men with inflammatory diseases. 15 In our patient, probably the epididymal cysts observed in both caputs may be related to the AAT-D. Sperm are produced in the testis but mature in the epididymis, where they stay for at least 15 days; in this organ they acquire lineal motility and suffer some biochemical changes known as “decapacitation,” a phenomenon that enables them for their long trip to the ovum.…”
Section: Discussionmentioning
confidence: 99%